Performance of bio-oil modified paving asphalt: chemical and rheological characterization - Wang, Chao; Xie, Tingting; Cao, Wei (Materials and structures, 2019)
Asphalt binders modified with bio-oils derived from various biomasses have been developed for addressing pavement sustainability and environmental concerns. This study evaluated the bio-binders modified with bio-oils derived from waste cooking oil, and was aimed for the chemical and rheological characterization under different oxidative aging conditions and the aging susceptibility of the bio-binders. The chemical analysis was based on saturates, aromatics, resins, and asphaltenes (SARA) fractionation, gel permeation chromatography (GPC), and thermogravimetric analysis (TGA). The rheological characterization consisted of multiple stress creep recovery, linear amplitude sweep, and elastic recovery tests. The results indicated that aging caused shift from the light components to the asphaltenes or heavy molecules. The bio-oil modification balanced the effect of aging by producing relatively well-dispersed asphalt systems in comparison to the petroleum control. According to the SARA and GPC analyses, the petroleum asphalt was less susceptible to aging. The TGA results suggested that once aged the bio-binders were less stable under high temperatures presumably due to thermal degradation of the bio-oil molecules. The addition of bio-oil lowered the rutting resistance and marginally reduced the elastic recovery potential; according to the corresponding evaluation parameters, the aging resistance of the bio-binders was similar or slightly lower as compared to the control. The bio-oil modification improved the fatigue cracking performance and also reduced the aging susceptibility within the context of fatigue resistance. The correlation between the chemical and rheological properties of the bio-binders were in line with the implications based on the colloidal model for petroleum asphalts.